Transcranial Direct Current Stimulation on Different Targets to Modulate Cortical Activity and Dual-Task Walking in Individuals With Parkinson’s Disease: A Double Blinded Randomized Controlled Trial - Wong, Pei-Ling; Yang, Yea-Ru; Huang, Shih-Fong; Fuh, Jong-Ling; Chiang, Han-Lin; Wang, Ray-Yau (Frontiers in Aging Neuroscience, 2022)
Background Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation to modulate cortical activity for improving motor function. However, the information of tDCS stimulation on different brain regions for dual-task walking and cortical modulation in Parkinson’s disease (PD) has not yet been compared. Objective The objective of this study was to investigate the effects of different tDCS targets on dual-task gait performance and cortical activity in patients with PD. Methods A total of 36 participants were randomly assigned to primary motor cortex (M1) tDCS, dorsal lateral prefrontal cortex (DLPFC) tDCS, cerebellum tDCS, or Sham tDCS group. Each group received 20 min of tDCS stimulation, except for the Sham group. Gait performance was measured by the GAITRite system during dual-task walking and single walking. Corticomotor activity of the tibialis anterior (TA) was measured using transcranial magnetic stimulation (TMS). The functional mobility was assessed using the timed up and go (TUG) test. Results All participants showed no significant differences in baseline data. Following the one session of tDCS intervention, M1 (p = 0.048), DLPFC (p < 0.001), and cerebellum (p = 0.001) tDCS groups demonstrated significant improvements in dual-task gait speed compared with a pretest. The time × group interaction [F(3, 32) = 5.125, p = 0.005] was detected in dual-task walking speed. The post hoc Tukey’s test showed that the differences in gait speed were between the Sham tDCS group and the DLPFC tDCS group (p = 0.03). Moreover, DLPFC tDCS also increased the silent period (SP) more than M1 tDCS (p = 0.006) and Sham tDCS (p = 0.002). Conclusion The results indicate that DLPFC tDCS exerted the most beneficial effects on dual-task walking and cortical modulation in participants with PD. Clinical trial registration [http://www.thaiclinicaltrials.org/show/TCTR20200909005], Thai Clinical Trials Registry [TCTR20200909005].